Implicit Bias and Health Disparities Education in the Neonatal Intensive Care Unit - Dyess, Nicolle Fernández; Carr, Cara Beth; Mavis, Stephanie C.; Caruso, Catherine G.; Izatt, Susan; French, Heather; Dadiz, Rita; Bonachea, Elizabeth M.; Gray, Megan M. (American Journal of Perinatology, 2024)
Objective This study aimed to characterize implicit bias (IB) and health disparities (HD) education in neonatal–perinatal medicine (NPM), including current educational opportunities, resources, and barriers.Study Design A national web-based survey was sent to NPM fellows, neonatologists, and frontline providers after iterative review by education experts from the National Neonatology Curriculum Committee. Quantitative data were analyzed with chi-square and Fisher's exact tests. Qualitative data were evaluated using thematic analysis.Results Of the 452 NPM survey respondents, most desired additional IB (76%) and HD (83%) education. A greater proportion of neonatologists than fellows received IB (83 vs. 57%) and HD (87 vs. 74%) education. Only 41% of neonatologists reported that their institution requires IB training. A greater proportion of fellows than neonatologists expressed dissatisfaction with the current approaches for IB (51 vs. 25%, p < 0.001) and HD (43 vs. 25%, p = 0.015) education. The leading drivers of dissatisfaction included insufficient time spent on the topics, lack of specificity to NPM, inadequate curricular scope or depth, and lack of local educator expertise. A minority of faculty who were tasked to educate others have received specific educator training on IB (21%) and HD (16%). Thematic analysis of survey free-text responses identified three main themes on the facilitators and barriers to successful IB and HD education: individual, environmental, and curricular design variables.Conclusion NPM trainees and neonatologists desire tailored, active, and expert-guided IB and HD education. Identified barriers are important to address in developing an effective IB/HD curriculum for the NPM community.Key Points
Keywords: implicit bias; health disparities; neonatal–perinatal medicine; curriculum development